Characterization of the complete mitochondrial genome of Aphyocypris chinensis (Cypriniformes, Xenocyprididae), and its phylogenetic position in Cypriniformes. Issue 9 (2nd September 2021) - Kim, Sang Ki; Cho, Hee-Wook
Abstract: Aphyocypris chinensis Günther, 1868 is a small freshwater fish of the family Xenocyprididae (Cypriniformes). In this study, we determined its complete mitochondrial genome and phylogenetic position in Cypriniformes. The complete mitochondrial genome is 16, 608 bp in size, containing 13 protein-coding genes, two RNAs, 22 tRNAs, and a control region. It has the typical vertebrate mitochondrial gene arrangement. Our mitogenomic phylogeny revealed that A . chinensis belongs to Xenocyprididae, rather than Danionidae. This mitogenome information could play an essential role in resolving the conflict over its current taxonomic status in Cypriniformes.